Pulling the Plug: Software Project Management and the Problem of Project Escalation1 - Keil, Mark (MIS Quarterly, 1995)
Information technology (IT) projects can fail for any number of reasons and in some cases can result in considerable financial losses for the organizations that undertake them. One pattern of failure that has been observed but seldom studied is the IT project that seems to take on a life of its own, continuing to absorb valuable resources without reaching its objective. A significant number of these projects will ultimately fail, potentially weakening a firm’s competitive position while siphoning off resources that could be spent developing and implementing successful systems. The escalation literature provides a promising theoretical base for explaining this type of IT failure. Using a model of escalation based on the literature, a case study of IT project escalation is discussed and analyzed. The results suggest that escalation is promoted by a combination of project, psychological, social, and organizational factors. The managerial implications of these findings are discussed along with prescriptions for how to avoid the problem of escalation.